1997
DOI: 10.1063/1.118512
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between latent interface trap buildup and 1/f noise in metal–oxide–semiconductor transistors

Abstract: Articles you may be interested inSurface and core contribution to 1/f-noise in InAs nanowire metal-oxide-semiconductor field-effect transistors Appl. Phys. Lett. 103, 033508 (2013); 10.1063/1.4813850Correlation between the 1 ∕ f noise parameters and the effective low-field mobility in Hf O 2 gate dielectric nchannel metal-oxide-semiconductor field-effect transistors Appl. Phys. Lett. 85, 1057 (2004); 10.1063/1.1779967 1/f noise in n-channel metal-oxide-semiconductor field-effect transistors under different hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…22 Another possibility is that H ϩ ions formed during irradiation are captured by oxygen vacancies and represent a gate oxide trapped charge. 4,23 During annealing they are liberated and drift towards the interface. However, the contribution of captured hydrogen ions to ⌬N ot should be relatively small, since it has been shown that almost all oxide trapped charge is EЈ centers.…”
Section: H-w Modelmentioning
confidence: 99%
“…22 Another possibility is that H ϩ ions formed during irradiation are captured by oxygen vacancies and represent a gate oxide trapped charge. 4,23 During annealing they are liberated and drift towards the interface. However, the contribution of captured hydrogen ions to ⌬N ot should be relatively small, since it has been shown that almost all oxide trapped charge is EЈ centers.…”
Section: H-w Modelmentioning
confidence: 99%
“…A particularly intriguing possibility is that H ϩ -induced passivation of dopants in the Si surface layer may lead to a switch from buried to surface channel conduction. 4 In such a case, the latent increase in ⌬N it would not necessarily have to come as a consequence of the increase in the actual number of interface traps, but as a result of their increased influence on conduction in the p-channel region of our devices, as the current would move closer to the Si/SiO 2 interface. The reversible exchange of H ϩ between near-interfacial SiO 2 and Si, along with the reversible oxide-trap charge compensation by electrons, 11 may be responsible for rebound in ⌬N ot after the bias switch in Fig.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%
“…2 An interesting possibility is to attribute the LITB to retarded H ϩ transport through SiO 2 and Si and its interactions at or near the Si/SiO 2 interface 3 and/or in the Si surface layer. 4 Commercially processed oxides, as is our case, are plausible candidates for retarded H ϩ transport, during which the H ϩ is captured at traps associated with O vacancies, and released at later annealing times. 3,4 If we take the scenario of interface-trap formation by H ϩ reaction at the interface, we would have essentially the same mechanism as for conventional interface-trap buildup, 6 but slowed down.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%
See 2 more Smart Citations